Engaging Male Youth in Karamoja, Uganda: An examination of the factors driving the perpetration of violence and crime by young men in Karamoja and the applicability of a communications and relationships program to address related behavior (Tufts Archival Research Center, 2018)
Engaging Male Youth in Karamoja, Uganda: An examination of the factors driving the perpetration of violence and crime by young men in Karamoja and the applicability of a communications and relationships program to address related behavior, by Elizabeth Stites et al